2016
DOI: 10.1037/cpp0000151
|View full text |Cite
|
Sign up to set email alerts
|

Rapid-response behavioral triage for tics (RRBTT): A 2-week clinical case series.

Abstract: Traditional behavioral treatments for tic disorders in youth require 8 sessions delivered over 10 weeks. Treatment duration represents a major barrier for patients and families, hinders direct comparisons between behavioral treatment and front line medication, and may motivate front line pharmacotherapy in place of behavioral interventions. The current case series describes an accelerated rapid-response behavioral triage for tics (RRBTT) and treatment outcomes. A retrospective chart review was conducted on cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…Results showed that four out of five patients reported significant reductions in YGTSS scores, and two of the five patients were clinical responders as measured by the CGI-I. Similarly, Kennedy et al (2016) administered CBIT to 10 patients with TD or CTD in eight sessions conducted over a 2-week period. Results showed that the YGTSS scores were reduced 41%, and half of the participants were classified as clinical responders on the CGI-I.…”
Section: Remote Deliverymentioning
confidence: 99%
“…Results showed that four out of five patients reported significant reductions in YGTSS scores, and two of the five patients were clinical responders as measured by the CGI-I. Similarly, Kennedy et al (2016) administered CBIT to 10 patients with TD or CTD in eight sessions conducted over a 2-week period. Results showed that the YGTSS scores were reduced 41%, and half of the participants were classified as clinical responders on the CGI-I.…”
Section: Remote Deliverymentioning
confidence: 99%
“…Dissemination efforts have included adaptations of CBIT for use in pediatrics and neurology practices (Ricketts, Gilbert, et al, 2016), and for utilization by occupational therapists (Rowe et al, 2013). Brief and intensive forms of CBIT have been developed (Blount et al, 2014(Blount et al, , 2018Kennedy et al, 2016), as well as self-help online (PsycTech Ltd, n.d.) and video adaptations (Specht et al, 2017) to be used at home. Despite efforts to make CBIT more available, a large portion of affected individuals with chronic tic disorders do not have access to CBIT trained providers.…”
Section: Domain 1 How To Increase Access To Cbitmentioning
confidence: 99%